Total Productive Maintenance Assessment on Discrete Manufacturing System - Mohd Fairozlan Bin Ahmad Tarmizi, Mohd Fairozlan (2008)
This project focuses on improvement and improvisation of a manufacturing line by using Total Productive Maintenance concept as tools to help reduce the amount of losses due to machine breakdown and other blockage during production. The main objective of this project is to reduce the frequency of breakdown in order to avoid losses to scrap and also to increase internal supply chain performance in a given four month period.